2020
DOI: 10.18290/rpsych.2019.22.2-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between study addiction and examination stress among students of music academies

Abstract: Previous studies have shown that study addiction is related to worse academic performance among music academy students as well as in the general population of students, suggesting that excessive examination stress may impair their performance on exams. The aim of this study was to investigate the relationship between the newly developed concept of “study addiction” and examination stress among students of music academies. Study addiction has been defined within the framework of theory and research on work addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 28 publications
(67 reference statements)
7
23
0
Order By: Relevance
“…Study addiction was found to be positively associated with learning engagement, at least to some extent; it was also positively associated with other variables including low extraversion and high social anxiety, specific aspects of studying (longer learning time and lower academic performance), and indicators of decreased wellbeing (impaired general health, decreased quality of life and sleep quality, and higher perceived stress). These findings are similar to those of Atroszko (2015), , Atroszko, Andreassen, et al (2015), and Wróbel (2020) in suggesting that study addiction is pathological. These and the results of other studies on the study and work addiction support the notion that intensive, prolonged overinvolvement in work-related activities may exact high costs in terms of health, quality of life, productivity, and social relations (Atroszko, , 2019Griffiths et al, 2018).…”
Section: Study Addictionsupporting
confidence: 89%
See 1 more Smart Citation
“…Study addiction was found to be positively associated with learning engagement, at least to some extent; it was also positively associated with other variables including low extraversion and high social anxiety, specific aspects of studying (longer learning time and lower academic performance), and indicators of decreased wellbeing (impaired general health, decreased quality of life and sleep quality, and higher perceived stress). These findings are similar to those of Atroszko (2015), , Atroszko, Andreassen, et al (2015), and Wróbel (2020) in suggesting that study addiction is pathological. These and the results of other studies on the study and work addiction support the notion that intensive, prolonged overinvolvement in work-related activities may exact high costs in terms of health, quality of life, productivity, and social relations (Atroszko, , 2019Griffiths et al, 2018).…”
Section: Study Addictionsupporting
confidence: 89%
“…Study addiction has been conceptualized as a potential early form of, or precursor to, work addiction (Atroszko, 2015; Atroszko, Andreassen, et al, 2015). It has been defined by analogy to a recently proposed general definition of work addiction ascharacterized by a compulsion to study and preoccupation with study activities leading to significant harm and distress of a functionally impairing nature to the individual and/or other significantly relevant relationships (friends, family).…”
Section: Study Addictionmentioning
confidence: 99%
“…In this study we used a 7-point Likert-type response scale, ranging from 1 (I am not at all engaged) to 7 (I am completely engaged). The Polish version of the scale showed good validity in the previous research (Atroszko, 2015;Atroszko et al, 2015;Atroszko et al, 2019b;Lawendowski et al, 2019).…”
Section: Methodsmentioning
confidence: 57%
“…The Likert-type response scale ranged from 1 (never) to 5 (always). The scale has demonstrated good construct validity and reliability in previous studies (Atroszko, 2015;Atroszko et al, 2015Atroszko et al, , 2016aAtroszko et al, 2019b;Lawendowski et al, 2019). In the present study, single-factor structure was confirmed in the Polish sample (MLR estimator, χ 2 (14) = 90.19, p < .001, RMSEA = .070, 90% CI RMSEA = .056-.084, CFI = .945, SRMR = .031) as well as in Indian sample (MLR estimator, error terms of items 1 and 2 cor-related, χ 2 (13) = 23.35, p = .038, RMSEA = .052, 90% CI RMSEA = .012-.086, CFI = .927, SRMR = .046).…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation